Response of different plant functional types to environmental variability on Marion Island : quantifying diurnal patterns over a seasonal cycle using the photochemical reflectance index - Zietsman, Alta (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.